Gaya Bahasa Sarkasme dalam Kolom Komentar Instagram DPR RI (@dpr_ri) - Nabilah Syafendra; Devi Ismawati; Reginata Jennike MHB; Tri Utari (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
In the use of language, of course there is a certain style of language that humans use when interacting, in this case is to comment on an Instagram upload. The language style is used to express all ideas, intentions, feelings, and thoughts related to the uploads seen by the Instagram users. The approach used in this research is a qualitative approach. The method used is the method of content analysis. In this study, the data are comments that contain sarcasm, while the source of the data comes from the DPR RI's Instagram comment column (@dpr_ri). Data collection begins with collecting information related to existing comments, then documenting by taking screenshots. Then, the data that has been found is analyzed using sarcasm language style. There were 24 data on the use of sarcasm in the comments column for the DPR RI Instagram account. There are various forms of sarcasm comments in the DPR RI Instagarm comments column, including: 1) containing ridicule, ridicule, and satire, 2) contradicting language meanings, 3) containing bitterness and not pleasing to the eye or hearing, 4) containing reproach that bitter.